P1774CONVERSION FROM TWICE-DAILY TACROLIMUS (TAC-IR) TO ONCE-DAILY EXTENDED RELEASE TACROLIMUS (LCPT) IN EVEROLIMUS TREATED STABLE KIDNEY TRANSPLANT RECIPIENTS. (6th June 2020) - Cseprekal, Orsolya; Marton, Adrienn; Török, Szilárd; Patonai, Attila; Földes, Katalin; Wagner, Laszlo; Molnar, Miklos Zsolt; Mathe, Zoltan; Kobori, Laszlo; Remport, Adam
Abstract: Background and Aims: Stable kidney transplant patients (KTX) treated according to TRANSFORM study protocol (TAC-IR + everolimus (EVR) + corticosteroid) were converted from twice daily TAC-IR to novel (MELT-dose) once-daily tacrolimus formulation (LCPT) on a 1:0.7 total daily dose (TDD) basis. Tolerability, safety, and trough level (Co) – TDD characteristics of the conversion (CV) was analyzed in a single center retrospective observational study. Method: Between Sep. 2017 and Aug. 2018 38 KTX recipients were included. Pre- and post-CV TAC TDD, Co and TAC Co/D as well as EVR TDD and Co data were evaluated 4, 2 weeks before and 4 consecutive times after CV (94 (74-112 median IQR) post-transplant days). Pre- and post-CV eGFR, routine lab parameters and occurrence of adverse events were also investigated. Results: In one patient 2 weeks after CV EVR was stopped due to infection, 37 KTX (males 22 (58%), age 54 (42-63) years) finished the entire observational period. According to CV protocol the median TDD of LCPT was lower than pre-CV TAC-IR at each visit: 4.5(3.5-7) mg/day pre-CV versus 3.5 (2.5-5), 3.6 (2.5-5), 3.5 (2.5-5) and 3.5 (2-5) (p<0.001) post-CV. Mean TAC Co decreased from pre-CV Co 7.8 (6.4-9.5) ng/ml to 6.7 (4.8, 8.6), 7.0 (5.2, 9.6), 6.5 (5.7, 8.4) and 7.2 (5.4, 8.7) (p<0.001). LCPT Co /TDD did not change: 1.6 (1.1-2.5) pre- and 2.1 (1.1- 2.9), 2.1 (1.1- 4.1), 1.6 (1.3- 3.5), 2.0 (1.4-4.1) (p = 0.18) post-CV. EVR Co /TDD (1.6 (1.3-2.1), 1.6 (1.3; 2.3), 1.6 (1.3-2.0), 1.6 (1.2-2.2)) remained similar to pre-CV: 1.6 (1.4- 2.4) (p = 0.65). There was no change in eGFR, hemoglobin levels and no drug related adverse event was observed during the study period. Conclusion: Conversion from TAC-IR to LCPT in everolimus treated stable KTX recipients resulted in a significant post-CV decrease in TAC- Co, whilst Co/TDD remained unchanged. The conversion was safe and had no effect on EVR Co and TDD. Further investigations are needed to define optimal TAC-IR to LCPT conversion dose rate.